1995
DOI: 10.1007/bf01439579
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent idiopathic scoliosis as developmental instability

Abstract: Adolescent idiopathic scoliosis is the most common spinal deformity affecting children, with a prevalence from mass screening programmes of 1-3%. Despite centuries of study, it remains a problem with no generally accepted theory of aetiology, and disagreement on its natural history and management. Because the deformity consists ultimately of gross left-right asymmetry, a study was undertaken to test the hypothesis that it might be a manifestation of developmental instability. Palmar dermatoglyphics in 112 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Another question is why the stage of skeletal maturity correlates so highly with the curve acceleration phase, particularly at CAP 0 to +6. Does this occur because skeletal maturation is a better reflector of longitudinal growth with the spine becoming unstable from rapid growth leading to curve progression, as suggested by Goldberg et al 22,23 ? Is it because the vertebral apophysis and growth plate is more susceptible to Heuter-Volkmann compressive growth inhibition at this stage, or is some other mechanism at work?…”
Section: Use Of the Curve Acceleration Phasementioning
confidence: 98%
“…Another question is why the stage of skeletal maturity correlates so highly with the curve acceleration phase, particularly at CAP 0 to +6. Does this occur because skeletal maturation is a better reflector of longitudinal growth with the spine becoming unstable from rapid growth leading to curve progression, as suggested by Goldberg et al 22,23 ? Is it because the vertebral apophysis and growth plate is more susceptible to Heuter-Volkmann compressive growth inhibition at this stage, or is some other mechanism at work?…”
Section: Use Of the Curve Acceleration Phasementioning
confidence: 98%
“…The hypothesis being tested was that scoliosis was a manifestation of developmental instability, rather than a specific disease process, a non-specific response to physiological stress, occurring under a variety of environmentally stressful conditions [45,46]. Preliminary work here and elsewhere had shown that patients with AIS showed more and greater asymmetry over a large variety of paired anatomical features than did normal controls [47][48][49][50]. The question asked was: does the back surface itself and hence the torso, follow the same pattern of asymmetry?…”
Section: Aetiologymentioning
confidence: 99%
“…Furthermore, the degree of scoliosis was re-evaluated by measurement of the Cobb angle (Goldberg et al, 1995) by tracing a line parallel to the upper boundary of the top vertebra and another line on the bottom edge of the adjacent lower vertebra and measuring the angle with a goniometer (CARCI, Brazil). The intersection of these two lines determined the angle of deviation of the spine.…”
Section: Assessment Proceduresmentioning
confidence: 99%